The Magic Mountains : Hill Stations and the British Raj. - Kennedy, Dane (University of California Press, 2022)
Perched among peaks that loom over heat-shimmering plains, hill stations remain among the most curious monuments to the British colonial presence in India. In this engaging and meticulously researched study, Dane Kennedy explores the development and history of the hill stations of the raj. He shows that these cloud-enshrouded havens were sites of both refuge and surveillance for British expatriates: sanctuaries from the harsh climate as well as an alien cultur.
Description based upon print version of record.
Keywords: Hill stations -- India -- History.; India -- Description and travel.; Summer resorts -- India.; India -- History -- British occupation, 1765-1947.; Inde -- Descriptions et voyages.; Stations d'été -- Inde.; Inde -- Histoire -- 1765-1947 (Occupation britannique); Hill stations.; Summer resorts.; Travel.; India.; 1765-1947; History.